Construction of Pictorial Dictionary for the Concept of Shape and Size in Early Mathematics Education of 4 Years Old Children: Pembinaan Kamus Bergambar bagi Konsep Bentuk dan Saiz dalam Pendidikan Matematik Awal Kanak-Kanak 4 Tahun - Mohd Hanizam, Nur Sabrina; Omar, Romarzila; Ramli, Rosliza (Jurnal Pendidikan Bitara UPSI, 2022)
This study aims to look at the needs and effectiveness of the use of photography dictionaries for the concept of shape and size in Mathematics Education towards children’s learning in nursery. The objective of this study is to analyze the requirements of learning the concept of shape and size, designing and developing a dictionary of Early Mathematics Education for the concept of shape and size and also evaluating the usability of a photo dictionary for the concept of shape and size in Early Mathematics Education. This study was conducted using the design and development research (DDR) method in building a photo dictionary for the learning of shape and size concepts. The study sample for phase one was 100 respondents comprising parents, nursery teachers and Early Childhood Education (ECE) students for questionnaires while in phase two and three were nursery teachers and an expert in Science, Technology, Engineering and Mathematics (STEM) fields to be interviewed. The findings from this study found that the use of photo dictionaries for the concept of shape and size is still relevant for use by educators and carers in providing learning as a teaching aid to children. The photo dictionary produced should be in accordance with the age of the child and be able to give them a good understanding. The use of this photo dictionary should also be guided by educators or guardians so as not to occur confusion between children. Therefore, teachers and parents play a high role using teaching aid which is effective and meaningful in children’s learning so that they acquire the knowledge without any willingness or confusion.